INTERRELATION OF THE MONEY AND CAPITAL MARKETS - Jasienė, Meilė; Paškevičius, Arvydas (Ekonomika, 2009)
The structure of financial markets is a constantly developing organism displaying an ever-changing pattern of the weight in the overall financial market structure of its constituents such as capital market, money market and the market of financial derivatives as a product of thetwo markets. The changes and the new developments are caused by a vast number of reasons and factors including the interaction of the markets concerned. The structural changes taking place in the financial markets and the related forecasts are of great importance to the investors and investment portfolio managers. The financial markets of Lithuania have already become an integral part of the global financial system therefore the authors of the present study did not limit the scope of the survey exclusively to the Lithuanian markets and took a broader view by carrying out a survey of the financial market segments such as capital and money markets of a number of Eastern European, Western European, North American States and the Pacific Ocean region, also the trends of the structural developments as well as the factors causing the processes.The purpose of the present study was to assess whether capital and money markets develop in parallel, i.e., the development of one market creates the conditions favourable for the growth and development of the other, or the two markets perform as competitors. The object of the survey: money and capital markets of East European, West European, North American and Pacific Ocean region countries. Methods used: analysis of the research literature, statistical grouping, correlation analysis.